Trauma Healing: Anak-anak Korban Banjir dan Longsor di Batu Bala dan Langgai, Kab. Pesisir Selatan, Sumatera Barat - Putra, Ahmad; Hifzhi, Husnul; Prasetya, Bima; Ahmad, Rapi; Rahmadhani, Nia (Department of Islamic Guidance and Counseling, 2024)
This research started from the flood and landslide disaster in Batu Bala and Langgai Villages, Sutera District, Pesisir Selatan Regency, West Sumatra. The rain that never stopped meant that the water supply could no longer be held by the river. As a result, lives were lost, people disappeared and people's houses were damaged. The serious problem behind this disaster is the emergence of fear and anxiety experienced by the survivors, especially children, this is because this disaster is the worst disaster and they never imagined the impact would be this severe. One of the efforts provided so far is trauma healing, which is coordinated by male students from the Batu Bala and Langgai areas and also participated in by the local community. The research method that the author uses is a qualitative method, supplemented by observations and interviews, solely to improve this article. The results of this research show that; first, students provide play therapy for victims, especially school age children, second, entertain children with dance therapy, third, hold book reading events, especially reading books by Islamic figures who have extraordinary patience, fourth, hold food events together with children who were victims of floods and landslides.